1997
DOI: 10.1093/nar/25.24.5052
|View full text |Cite
|
Sign up to set email alerts
|

The methylated DNA binding protein-2-H1 (MDBP-2-H1) consists of histone H1 subtypes which are truncated at the C-terminus

Abstract: The methylated DNA binding protein-2-H1 (MDBP-2-H1), present in rooster liver, is a member of the histone H1 family which inhibits transcription by binding selectively to methylated promoters. Here we have determined the primary structure of MDBP-2-H1. A comparison between histone H1 and MDBP-2-H1 was achieved by analyzing reversed phase HPLC-purified and V8-digested proteins by mass spectrometry and/or microsequencing. In rooster liver the most abundant histone H1 subtypes are H1 01 and H1 11L. Similarly, MDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…These sequence-specific DNA-binding proteins show increased binding to these sites in their CpG-methylated form. The sequence specificity of the binding site distinguishes these proteins from methylated DNA-binding proteins, such as MeCP1, MeCP2, DBP-m, and MDBP-2-H1 (22,(32)(33)(34)(35). We demonstrated that the MDBP/RFX could bind to a sequence at the very beginning of the ␣2(I) gene first exon in the rodent and human genomes in a methylation-dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…These sequence-specific DNA-binding proteins show increased binding to these sites in their CpG-methylated form. The sequence specificity of the binding site distinguishes these proteins from methylated DNA-binding proteins, such as MeCP1, MeCP2, DBP-m, and MDBP-2-H1 (22,(32)(33)(34)(35). We demonstrated that the MDBP/RFX could bind to a sequence at the very beginning of the ␣2(I) gene first exon in the rodent and human genomes in a methylation-dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…Such assignment of LHL trypsin‐digested peptides seems to reflect the presence of the H1 and H5 histone sequences in the LHL1 and only H1 histone sequences in the LHL2. Of special interest is a high individual ion sore for the SETAPAPAAEAAPAAAPAPAKA peptide (Table 2) present at the very N‐terminal end of histone H1.c′ (Shannon and Wells, 1987) and MDBP‐2‐H1 (Schwarz et al., 1997). Therefore, it seems that a complex of duck LHL may also contain N‐terminal sequences resembling those of the chicken H1.c′.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to abundant histone H5, the avian erythrocyte linker histones may include up to eight H1 histone variants which can exhibit qualitative and quantitative differences among various species. Linker histone variants H1.z, H1.a, H1.a′, H1.b, H1.b′, H1.c, H1.c′, H1.d and H5 migrate in that order in an acid‐urea polyacrylamide gel (Pałyga, 1991a; Shannon and Wells, 1987). When a gel pattern of linker histones in avian population is analyzed, the allelic isoforms of polymorphic variants with a shifted electrophoretic mobility due to the differences in their molecular weight and/or net charge are occasionally detected.…”
Section: Introductionmentioning
confidence: 99%
“…Histone H1 colocalized with 5‐methylcytosine (Ball et al ., 1983) and bound preferentially to CpG‐methylated DNA irrespective of DNA sequence (Jost and Hofsteenge, 1992; McArthur and Thomas, 1996). Several reports have established a positive correlation between DNA methylation, binding of histone H1 and transcriptional repression (Levine et al ., 1993; Johnson et al ., 1995; Schwarz et al ., 1997). In contrast with these observations, it was reported that Histone H1 has no preference for methylated DNA (Campoy et al ., 1995) and no role in methylation‐associated gene silencing (Barra et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%